Practical Considerations for Paul Ricoeur’s “Transformation of Subjectivity” In The Indonesian Context - John Christianto Simon; Adrianus Yosia (Sekolah Tinggi Theologia Jaffray, 2020)
Hermeneutics is the task of interpreting in the area of action. The purpose of interpreting is the emancipation of a better and fairer life. One of the hermeneutic thinkers is Paul Ricoeur. Ricoeur’s hermeneutic project is built on criticism of the subject. Its purpose of producing a “transformation of subjectivity.” By undermining the illusion of the absolute, exploitative, and dominant matter manifested in the homo oeconomicus. This transformation of subjectivity can be used to analyze the area of action in public space. There are three hermeneutical tasks. The first is a hermeneutical task in poverty; the second is its task in the context of environmental damage (ecology). And the third is its task in the context of fighting economic and political injustice. All hermeneutical tasks are supported by the basic ethics of emancipation, namely “love and justice.”